Frontières Et Dynamiques Socio-Spatiales En Afrique : Une Analyse À Partir Des Frontières Sud- Camerounaises - Abdoulay Mfewou; Hervé Tchekote; Josephine Lemouogue (European Scientific Journal, ESJ, 2018)
This article focuses on the openness and socio-economic dynamics associated with the meeting of different communities from many inland territories of Africa: on the borders of South Cameroon, northern Equatorial Guinea and North of Gabon, attracted by the oil windfall. The study illustrates the effectiveness of "living together" in this vast sub-region. It shows how development is based on the organization of trade that is not simply based on the differences between national systems, but on the establishment of South- South relations. While the challenges based on planning on these cross-border spaces is indispensable, local elected representatives are trying to set-up networking arrangements for cross-border communities. Border management makes it possible to ensure security, counter-threats to people and economic prosperity. The construction of a motorable high-way and the implementation of treaties on the opening of borders signed between the States since the 16th of March 1994 deemed at facilitating the free movement of economic actors, while many still consider the arrival of foreigners in these Eldorado as an invasion.